Restitution of Property and Religious Discrimination in Eastern Europe - Riegger, Maria (Refuge: Canada’s Journal on Refugees, 2000)
This work centers on the religious liberty situation in Eastern Europe, including countries such as Hungary and Romania. The article discusses disputes over property rights and titles since the fall of communism, focusing on how these have been closely interconnected with the religious background and history of diferent ethnic groups.